Ecology and Mary: An Ecological Theology of Mary as the New Eve in Response to the Church’s Challenge for a Faith-Based Education in Ecological Responsibility - Thurmond, Gloria J. (Catholic Education: A Journal of Inquiry and Practice, 2007)
The Church’s interpretation of the current ecological crisis as a moral crisis is the catalyst for this essay, which proposes a newly constructed faith-based model for ecological dialogue and education. The exploration and reinterpretation of the traditional Church doctrine of the Virgin Mary as the new Eve provides a theme from which an ecological theology of Mary is constructed. Papal and Episcopal statements that call for a moral concern and response to the growing urgency of the ecological crisis are discussed in order to promote awareness of the involvement of the Church’s leadership in the issue. Analyses and interpretations by scholars in the second century Church on the doctrine of Mary as the new Eve are presented and reinterpreted to create a viable model with the potential to nurture ecological awareness and responsibility in the contemporary Church. The construction of an ecological Marian theology is approached through review and analysis of the 1974 visionary pastoral letter of Pope Paul VI, Marialis Cultus (To Honor Mary), the writings of Catholic feminist theologian and Sister of St. Joseph Elizabeth Johnson, Catholic Ecuadorian-American theologian Jeanette Rodriguez, and those of other major feminist, womanist, and liberationist theologians.